Supplier management: perspectives from large manufacturers in Thailand. (4th February 2008) - Phusavat, Kongkiti; Kanchana, Rapee
The study aims to prioritise important criteria, as a baseline, for supplier selection and monitoring. The need for this study stems from an ongoing trend of outsourcing in Thailand and the dynamic nature of supplier management. This study relies on the companies' feedbacks from four areas (i.e. automotive and auto parts, electrical and electronics, food and petrochemical) that have contributed greatly to the country's economic development. The questionnaire is developed for data collection. The large manufacturers, members of the Federation of Thai Industries or FTI with more than 200 employees, were asked to rate the level of importance on each of the seven criteria (i.e. quality, cost, delivery, responsiveness, management, technical service and environment/safety) and their corresponding detailed subjects for three outsourced work (i.e. production-supply, maintenance and transportation). The analysis indicates that the seven criteria are rated slightly differently among these outsourcing circumstances. The criteria ranking, appearing to be consistent with previous work, are expected to help relevant public agencies formulate viable programmes for strengthening Small- and Medium-Sized Enterprises (SMEs). The FTI can possibly use these results to encourage a supplier-development programme for its clusters. This should bring about better value-chain management for large manufacturers.